PENGARUH KOMPENSASI, ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MULTI ZHEKINAH CONSULTANS DI KOTA SORONG - Melannesya F. Jitmau; Makarius Bajari; Jan Felarius Tata (Lensa Ekonomi, 2025)
This study aims to determine the effect of compensation, work ethic and work environment on employee performance at PT. Multi Zhekinah Consultans in Sorong City. The type of research used is a quantitative descriptive approach. The population in this study were all employees of PT Multi Zhekinah Consultans Company as many as 34 respondents. The method used in determining the sample was the saturated sampling method. The data collection method used primary data by conducting observations, interviews, and distributing questionnaires. This research instrument used a Likert scale with a data analysis method, namely multiple linear regression analysis using SPSS statistical cofhcare. The results of the study indicate that the compensation variable has a partial effect on employee performance, then work ethic has an effect on employee performance while the work environment does not have a partial effect on employee performance. The results of the study showed that compensation, work ethic and work environment simultaneously have an effect on employee performance.